Medical treatment of patients with gynecologic cancer during the COVID-19 pandemic. Issue 8 (21st August 2021) - Palluzzi, Eleonora; Corrado, Giacomo; Marchetti, Claudia; Bolomini, Giulia; Vertechy, Laura; Bottoni, Carolina; Distefano, Mariagrazia; Scambia, Giovanni; Ferrandina, Gabriella
Abstract : Background: During the COVID-19 pandemic, cancer care had to be reorganized; national and international recommendations were published to manage anticancer treatments safely and to reduce the risk of SARS-CoV-2 infection for patients and health workers. Objective: To evaluate whether the adoption of recommendations for the management of patients with gynaecologic cancer receiving treatment during the pandemic resulted in containment of infections and continuing oncologic care. Methods: Based on the published recommendations, and according to the local Health Direction guidelines, we developed and drafted a security protocol to modify access of patients with gynaecologic cancer to the "Fondazione Policlinico Agostino Gemelli-IRCCS, Rome" between February 1 and April 30, 2020 and compared results with the corresponding 3 months of 2019. Results: Between February and April 2019, we registered 3254 admissions, including 2253 patients receiving intravenous chemotherapies, 298 receiving oral therapies, and 703 having hospital visits. Between February and April 2020, we registered 3213 admissions, including 2221 patients receiving intravenous chemotherapies, 401 receiving oral therapies, and 591 having hospital visits. Oral treatments and general visits were different in the two time periods (p<0.001). Despite the elevated patient flow, only one patient (0.1%) tested positive for COVID-19 and there were no cases among healthcare staff. Conclusions: Based on the adopted security protocol we provided continuity of care for all patients and limited the spread of the COVID-19 infection.